Optimization Extraction of Scandium from Scandium Concentrate with Titanium Dioxide Wastewater by Response Surface Methodology - Xiao, Junhui; Zhong, Nanlan; Cheng, Renju; Zhang, Junhui (Journal of sustainable metallurgy, 2024)
Scandium concentrate and titanium dioxide wastewater (TDWW) all belong to waste, especially TDWW belongs to hazardous waste, it is urgent to find a more efficient and safer treatment method to deal with them, and both waste acid and waste ore contain scandium. The use of waste acid as a leaching agent can achieve the synergistic recovery effect of scandium. First, the leaching temperature, time, and liquid–solid ratio are found to be significant factors through single-factor tests. Then, the test program is designed by using the Box Behnken unit of Design Expert software to explore the relationship between each factor including leaching temperature (℃), leaching time (h), and liquid-to-solid ratio (mL/g). The results show that the interaction between leaching time and liquid–solid ratio was the strongest. The second-order regression model equation generated by the software can well predict the leaching effect of scandium. The scandium leaching efficiency reaches 85.30%, and the scandium content in the leaching residue decreases to 10.24 g/t under the optimal conditions: leaching temperature of 70 ℃, leaching time of 2.0 h, and liquid–solid ratio 8.7 mL/g. The finite element analysis is to simulate the mineral roasting process and the temperature field changes are always present. Graphical Abstract